Genes NLRs candidatos para estudos de resistência à nematoides em Coffea canephora P. ex Fr. e Psidium guajava L. - Cardozo, Layra de Medeiros (2022)
Coffea canephora and Psidium guajava are agroeconomically important species that suffer productivity losses caused by root-knot nematodes. The identification of orthologous genes to resistance genes and molecular knowledge about them, contribute to the understanding of the plant-pathogen interaction and to more effective strategies in plant improvement. The NBSLRR gene family is the main class of resistance genes and is extensively studied in several plant genomes to search for resistance genes. This work aim was to identify and characterize genes of the NBS-LRR class (NLRs) in C. canephora and P. guajava, in addition to performing phylogenetic and diversity analyses. By means of bioinformatics tools and methods, identification and characterization of NLRs genes and construction of phylogenetic trees from maximum likelihood analysis in the two species were carried out, in addition to NLR polymorphism analyzes and the diversity of these genes in genotypes from the germplasm collection of C. canephora from the south of Espírito Santo. 649 and 279 NLR genes were identified in coffee and guava, respectively, and showed diversity in their characteristics. In C. canephora there was a greater amount of non-TIR genes (NLRs genes with domains CC-NBSLRR, CC-NBS, X-NBS-LRR, X-NBS, RPW8-NBS-LRR, RPW8-NBS, NBS-LRR and NBS), while in P. guajava the highest amount was TIR (NLRs genes with TIR-NBS-LRR and TIRNBS domains). 18 coffee NLRs genes and 18 guava NLRs genes are promising analogues of resistance genes (RGAs) with emphasis on evm.model.ctg40.285. This locus clustered closely into a clade with the protein encoded by Gro1-4 that confers resistance to Globodera Roschiensis. Diversity of NLR genes was observed in the analyzed C. canephora germplasm. In this way, the study contributed to the knowledge, identification and characterization of the NBS-LRR family in plants, in addition to selecting promising orthologs of resistance genes through phylogeny. Diversity analysis in C. canephora demonstrated the polymorphisms of the NLRs genes germplasm of C. canpehora botanical variety conilon.